2023
DOI: 10.1177/03000605231204477
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in patients with rheumatoid arthritis: association with quality of life, fatigue, depression levels, functional disability, disease duration, and activity: a multicentre cross-sectional study

Wesam Gouda,
Mona Mokhtar,
Seham A. Elazab
et al.

Abstract: Objective To investigate the correlations between pain, quality of life, fatigue, levels of depression, disability and activity, and sleep quality and common sleep disorders in patients with rheumatoid arthritis (RA). Methods This multicentre, cross-sectional study enrolled patients with RA and sex- and age-matched control subjects. Clinical, sociodemographic, serological and therapeutic data were collected. Data from the Disease Activity Score (DAS28-CRP), the Epworth Sleepiness Scale (ESS), Pittsburgh Sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Studies also indicate that untreated OSA significantly reduces QoL, affecting social, emotional, and physical wellbeing [8,9]. There are similar findings in other systemic rheumatologic diseases, indicating that reduced quality of life and sleep disturbances are common, further underscoring the effects of these conditions on patient well-being [10].…”
Section: Introductionmentioning
confidence: 63%
“…Studies also indicate that untreated OSA significantly reduces QoL, affecting social, emotional, and physical wellbeing [8,9]. There are similar findings in other systemic rheumatologic diseases, indicating that reduced quality of life and sleep disturbances are common, further underscoring the effects of these conditions on patient well-being [10].…”
Section: Introductionmentioning
confidence: 63%
“…[10][11][12] In recent years, several studies have attempted to explore the correlation between RA disease activity and HRQoL. [13][14][15] Previous studies have shown a high consistency of results, with a negative correlation between disease activity and HRQoL. 15 It was also found that insufficient sleep, increasing age and mental health conditions are factors that impact the HRQoL of people with RA.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…12 Moreover, some previous studies also exhibit that sleep disorders and comorbidities (such as hypertension, hypothyroidism, and deficiency anemias) are linked with fatigue in RA patients. 13,14 However, the gap of the above studies is that the vast majority of these studies use a single scale for fatigue evaluation in RA patients. More importantly, few studies verify the consistency among different scales for fatigue evaluation in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored fatigue conditions and some fatigue-related risk factors (including disease-related, personal, social, and seasonal factors) in RA patients. [9][10][11][12][13][14] For example, one recent study shows that fatigue occurrence is 62%; meanwhile, education level and disease activity are related to fatigue score in RA patients. 9 Simultaneously, another study indicates that some factors are associated with fatigue in RA patients, such as age, disease duration, functional disability, quality of life, and so on.…”
Section: Introductionmentioning
confidence: 99%